2022
DOI: 10.1097/phh.0000000000001563
|View full text |Cite
|
Sign up to set email alerts
|

Telehealth and Public Health Practice in the United States—Before, During, and After the COVID-19 Pandemic

Abstract: Telehealth is the use of electronic information and telecommunication technologies to provide care when the patient and the provider are not in the same room at the same time. Telehealth accounted for less than 1% of all Medicare Fee-for-Service outpatient visits in the United States in 2019 but grew to account for 46% of all visits in April 2020. Changes in reimbursement and licensure policies during the COVID-19 pandemic appeared to greatly facilitate this increased use. Telehealth will continue to account f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Although remote interventions in occupational therapy were active before the COVID-19 pandemic ( American Occupational Therapy Association [AOTA], 2021 ), lockdowns precipitated a fast, broader transition to telehealth for worldwide health care ( World Health Organization, 2020 ). This transition created opportunities for many organizations and clinicians who continue to use telehealth, preferring video-based meetings for their ease of use and ability to reach more clients ( Neri et al, 2022 ). Recent research demonstrated the efficacy of telehealth-based occupational therapy services among various populations ( Little et al, 2021 ; Nissen & Serwe, 2018 ).…”
mentioning
confidence: 99%
“…Although remote interventions in occupational therapy were active before the COVID-19 pandemic ( American Occupational Therapy Association [AOTA], 2021 ), lockdowns precipitated a fast, broader transition to telehealth for worldwide health care ( World Health Organization, 2020 ). This transition created opportunities for many organizations and clinicians who continue to use telehealth, preferring video-based meetings for their ease of use and ability to reach more clients ( Neri et al, 2022 ). Recent research demonstrated the efficacy of telehealth-based occupational therapy services among various populations ( Little et al, 2021 ; Nissen & Serwe, 2018 ).…”
mentioning
confidence: 99%
“…For example, in the USA, teleconsultation went from accounting for less than 1% of Medicare primary care visits before 2020 to 46% of all visits in April 2020. 9 Similarly, in France, the national health insurance system started reimbursing teleconsultations in September 2018, but the use of teleconsultation actually took off during the COVID-19 pandemic: reimbursement claims counted 9.4 million teleconsultations in 2021 compared to only 80 000 in 2019, and in 2021, approximately 4% of all general practice visits were teleconsultations. 10…”
Section: Introductionmentioning
confidence: 99%
“…HCPs provide care and interact with interprofessional team members (e.g., nurses, social workers, and pharmacists) and patients use telehealth in new ways that potentially increase HCPs' stress while offering opportunities for intime communication and innovation [9,10]. Telehealth practice changes have significantly reshaped the landscape of healthcare provision for providers [11]. As highlighted by Smith et al (2019) in the Journal of Telemedicine and Telecare, HCPs now experience enhanced work flexibility, yet face challenges with altered patient interactions due to the lack of physical contact.…”
Section: Introductionmentioning
confidence: 99%
“…As highlighted by Smith et al (2019) in the Journal of Telemedicine and Telecare, HCPs now experience enhanced work flexibility, yet face challenges with altered patient interactions due to the lack of physical contact. They have had to quickly adapt to new technological demands, grapple with complexities in electronic documentation, and navigate evolving licensing and reimbursement policies [11]. Moreover, while telehealth has expanded access to diverse patient demographics, HCPs are also facing the possibility of increased screen-induced fatigue and burnout [9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation